Effet De Fumures Minérales Sur Le Rendement Et La Qualité Organoleptique Du Manioc (Manihot Esculenta Crantz) Dans La Zone De Savane Au Centre-Sud De Centrafrique - Ballot, Christiant Simplice Armand; Semballa, Silla; Atakpama, Wouyo; Yangakola, Tatiana Maryse; Bo-Mbi, Arnaud Doubro; Blavet, Didier; Zinga, Innocent; Wala, Kpérkouma; Batawila, Kolman; Akpagana, Koffi (European Scientific Journal, ESJ, 2016)
Aims - The farming intensification in Sub-Saharan Africa induced soil fertility and crop yields depletion such as cassava, a main food and an important source of income of farmers in Central Africa Republic. To transcend the soil fertility depletion and improve cassava yield, LaSBAD has initiate a study focused on the mineral fertilizers of cassava crops. Methods - Four types of fertilizer were tested: the urea (Co(NH2)2), the potassium sulfate (K2SO4), the potassium chloride (KCl) and the triple superphosphate (TSP). The methodology consisted in the physical and chemical analysis of soil, the cultivation, the application of mineral fertilizers and the harvest of cassava after 12 months. Additionally, the evaluation of the organoleptic propriety of raw tubers and cassava balls after the use of fertlizers were achieved throughout semi-strucrured interviews. Results - The contribution of nitrogen and phosphorus has increased very significantly cassava yield from 18.70 to 40.20 t/ha respectively for the control treatment (T0) and the best treatment obtained (T10). A significant interaction was observed between nitrogen (N) and potassium (K) inputs on yields. The increasing doses of potassium as potassium chloride (KCl) had reduced cassava plant growth and yield. According to respondents, the organoleptic proprieties of cassava were remain quite unchangeable by mineral fertilizers. Conclusion - The application of mineral fertilizer improved cassava yield and did not affected the organoleptic quality of the raw tubers and cassava ball. Nevertheless, further studies are needed to prevent soil degradation, namely the potential use of termite nest as natural fertilizers and legumes in association or rotation with other crops.